MEMBUMIKAN HUKUM ISLAM DI INDONESIA - Al Amruzi, Muhammad Fahmi (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2015)
The existence of Islamic law in Indonesia has long earned a place in public life. It is the law established in the midst of society and even became the offi cial legal state at the time of Islamic kingdoms until the beggining of VOC. When the Dutch managed to take over all the power of the Islamic kingdoms, the Islamic law began to be abolished gradually. After independence, Indonesian people began to dig his own laws independently and Islamic laws still exists and getting stronger. The Islamic law has its own power which can take the form in legisation, jurisprudence and public legal awareness. Islamic law has an important strategic position in the formation and preparation of Indonesia's national law. One effort to incorporate Islamic law into the national legal order is through the transformation of the values of Islamic law into the Indonesian National Legal System.